Aspects to Enhance in the Quality of Life of Parents of Children with Central Nervous System Tumors: An Omani Experience - Rahima Al-Ismaili; Khalid Al-Busaidi; Salah Al Awaidy; Abeer AL-Battashi (Dr. Sulaiman Al Habib Medical Journal)
Introduction: The diagnosis of childhood cancer profoundly affects the quality of life of parents and caregivers, and central nervous system tumors are no exception. This study aims to identify the key areas of impact and propose strategies for improvement. Methods: By using an interview framework based on the accredited World Health Organization quality of life assessment tool (WHOQOL-BREF), we conducted in-depth, in-person interviews with six Omani families, encompassing 12 parents. We focused on four core dimensions of quality of life: physical, emotional, and psychological wellbeing, and interpersonal relationships. The interview data were analyzed using the thematic coding approach. Results: Thematic analysis of the interviews identified four main areas of impact: 1) challenges in adjusting to the diagnosis, often accompanied by grief, 2) psychological distress, 3) disruption of social relationships, and 4) financial and occupational burdens, including difficulties in maintaining work–life balance. 4) Despite these challenges, the parents demonstrated a strong sense of spirituality and reliance on social support networks. Conclusion: There is a pressing need in Oman for a structured screening and support system for families facing a diagnosis of childhood CNS malignancies. Early interventions can help mitigate the psychological and social consequences of the diagnosis, ensuring optimal caregiving and improved therapy adherence.